Piece Work - Andersen, Ingrid (Book collections on Project MUSE., 2010)
Ingrid Andersen was born in Johannesburg, read for a degree in English literature at Wits and is presently completing her Masters. Her work has been published in literary journals for 16 years. Excision, her first volume of poetry, was published in 2004. Her influences include the French Romantic poets, Imagism and the writings of Basho. She is the founding editor of Incwadi, an SA journal that explores the interaction between poetry and image. An Anglican priest, she works in human rights, healing and reconciliation.